Working During the Pandemic: Headteachers’ Experiences in Primary and Junior High Schools in Accra Metropolitan Education Directorate - Okyere Amponsah, Rosina; Addai-Mununkum, Richardson; Adjei-Boateng, Emmanuel; Commey-Mintah, Priscilla; Darko Amponsah, Kwaku (Papers in Education and Development, 2024)
This study investigated occupational stress levels among headteachers within the Accra Metropolitan Education Directorate (AMED) overseeing Ghana’s public primary and junior high schools during the COVID-19 Pandemic. The sample included 79 individuals, with 67 respondents participating in the study. The research employed an explanatory sequential sampling methodology. The study findings indicated that neither gender nor age had a significant effect on occupational stress levels. Interviews with participants highlighted widespread challenges in adhering to safety protocols, such as congregating and improper use of face masks. Recommendations derived from the study include reducing job demands, enhancing management support, and increasing flexibility and control, which are potential strategies to effectively mitigate work-related stress in the future. Keywords: Age, basic level, gender, occupational stress, school managers